Seeing human resources of entrepreneurial firms in new ways - Cardon, Melissa S.; Knockaert, Mirjam; Anseel, Frederik; Burton, M. Diane (Journal of Business Venturing, 2026)
Despite ongoing interest in human resource management (HRM) in entrepreneurial organizations, we believe the moment is ripe to rethink notions of human resource management in ways that take advantage of the distinctive nature of entrepreneurial settings. A critical first step is recognizing that the people creating and building an entrepreneurial organization extend beyond the founders and include people who may or may not be employees. As such, rather than following traditional human resources (HR) research's focus on employees, HR research in entrepreneurial organizations must take a broader perspective. We propose a focus on “joiners”, people who, according to Roach and Sauermann (2015) , are a “distinct type of nonfounding entrepreneurial actors who are attracted to the startup work setting but have little desire to be founders themselves.” Joiners represent the human resources critical to venture progress. We argue that a research agenda focused on joiners that is pursued through explicitly understanding and engaging with the fundamental assumptions, debates, and conversations from an entrepreneurship perspective will yield novel questions and generate new insights. Through this editorial we hope to catalyze this important work by unpacking who joiners are and how they fit in the entrepreneurial context, highlighting the need for new research at the intersection of HRM and entrepreneurship, and suggesting novel questions, research opportunities, and methodologies related to HRM in entrepreneurial settings. Scholars have advanced our Understanding of human resource management (HRM) in entrepreneurial organizations from multiple perspectives. We believe the moment is ripe to rethink notions of human resource management in ways that take advantage of the distinctive nature of entrepreneurial settings, which will allow us to understand human resources of entrepreneurial firms in new ways. A critical first step is recognizing that the people creating and building an entrepreneurial organization extend beyond the founders and include people who may or may not be employees. We propose a definition of joiners that captures the original spirit of the term and emphasizes the people who are actively choosing an entrepreneurial work setting, remains agnostic to formal employment status, and focuses on the work that is being done: “ Joiners are non-founders who contribute physical and/or mental labor to a new venture and are subordinate to the founders ”. Our definition is well-suited to the dynamic nature of entrepreneurial firms that are navigating uncertain environments, in which more flexible and less formal labor contributions are needed than merely those provided by employees. By consequence, our definition of joiners includes employees, contractors, interns, freelancers and volunteers and excludes other stakeholders such as tech transfer and other entrepreneurial support organization staff, board members, investors, policy makers, customers, and suppliers. We also suggest it may be helpful to distinguish between “primary joiners” and “secondary joiners.” The first refers to the initial group of people who are in direct contact with founders and who are creating their role rather than inhabiting an established role. These individuals bring the human and social capital that determines an early venture's success. Other individuals who later join an entrepreneurial venture, particularly those who are not directly overseen by founders, can be referred to as “secondary joiners”, or if they are actually employed by the startup, simply as employees. We argue that the study of joiners merits fresh thinking that more explicitly takes into consideration the core aspects of entrepreneurship: that it involves uncertainty and dynamism, resource constraints and context dependence, informality, and social or interpersonal creation of opportunities, ventures, and systems. A traditional HR perspective is focused on employees within firms who are in a formal employment relationship, occupying defined roles, within a hierarchical reporting structure where there is a supervisor, a set of performance expectations, and a package of rewards. In contrast, an entrepreneurship perspective considers contributions from people who may be employees or contractors or non-contracted helpers, straddling the fuzzy boundaries of a new venture in roles and reporting relationships that are ambiguous and evolving, doing work that is uncertain and ever-changing, with risky and unknown outcomes, rewards, and career prospects. We highlight specific research questions focused on joiners from an HR versus an entrepreneurship perspective that warrant additional investigation and discuss the most appropriate methodologies for such study. Overall, while we acknowledge and commend the efforts of many scholars who have already explored issues related to joiners, we believe that more explicitly recognizing and engaging with the distinct focus, assumptions, debates, and conversations inherent to an entrepreneurship perspective, as well as taking a broader perspective on who is a joiner, will inspire new questions and uncover novel insights into human resources of entrepreneurial firms. We encourage work that advances a uniquely entrepreneurship-informed understanding of joiners and of HRM. • We re-define the term “joiners”, differentiate them from other stakeholders, and clarify their unique position in startups. • We encourage taking into consideration unique features of entrepreneurship in research on HRM in entrepreneurial firms. • We propose a set of novel questions related to HRM in entrepreneurial settings from an entrepreneurship-focused approach. • We discuss promising methodologies for investigating such questions.